Risk Factors for Polyvascular Involvement in Patients With Peripheral Artery Disease: A Mendelian Randomization Study - Dikilitas, Ozan; Satterfield, Benjamin A.; Kullo, Iftikhar J. (Journal of the American Heart Association, 2020)
Background Atherosclerosis in >1 vascular bed (ie, polyvascular disease), often a feature of peripheral artery disease (PAD), is associated with high morbidity and mortality. We sought to identify risk factors for polyvascular involvement in patients with PAD. Methods and Results We performed 2-sample Mendelian randomization using an inverse-variance-weighted approach, to assess 60 exposures including size and lipid content of atherogenic lipoproteins, blood pressure, glycated hemoglobin, and smoking as causal mediators for polyvascular disease in patients with PAD. Genetic instruments for these exposures were obtained from prior genome-wide association studies. Patients with PAD were from the Mayo Vascular Disease Biorepository, and polyvascular disease (ie, concomitant coronary heart disease, cerebrovascular disease, and/or abdominal aortic aneurysm) was ascertained by validated phenotyping algorithms. Of 3279 patients with PAD, 61% had polyvascular disease. Genetically predicted levels of the lipid content and/or particle measures of very small and small size very low-density lipoprotein, intermediate-density lipoprotein, and large low-density lipoprotein were associated with polyvascular disease: odds ratios (OR) of 1.80 (95% CI, 1.23-2.61), 1.70 (95% CI, 1.17-2.61), and 1.40 (95% CI, 1.09-1.80) per 1 SD increase in genetically determined levels, respectively. Both genetically predicted diastolic and systolic blood pressure were associated with polyvascular disease; OR per 10 mm Hg genetic increase in diastolic and systolic blood pressure were 1.66 (95% CI, 1.19-2.33) and 1.31 (95% CI, 1.07-1.60), respectively. Conclusions Lifetime exposure to increased lipid content and levels of very small and small very low-density lipoprotein, intermediate-density lipoprotein, and large low-density lipoprotein particles as well as elevated blood pressure are associated with polyvascular involvement in patients with PAD. Reduction in levels of such exposures may limit progression of atherosclerosis in patients with PAD.